Analisis Forgiveness Pasca Perceraian Orang Tua - Naila Syaqi Zulkarnain; Syira Aulia Akasyah; Nahdah Kamilah Faatin; Tri Artanti; Fatma Nofriza (Journal on Education, 2025)
Divorce for couples with children is a decision that affects not only the divorcing couple, but also the children. Some children take a long time to forgive their parents' divorce, so the purpose of this study is to explore the forgiveness process in children's recovery after their parents' divorce. This research method uses a descriptive approach through interviews. The subjects of this study are children who are victims of their parents' divorce, the number of subjects in this study is 2 people. The data collection tools used in this research are interview guide, observation and documentation. The research results show that the first subject feels disappointment and anger and is more likely to avoid forgiveness, while the second subject is more able to accept their situation. This study concludes that the forgiveness process is crucial for children after their parents' divorce, with the first subject having an avoidance motivation, namely to avoid the perpetrator, while subject "R" shows a benevolence motivation with an indifferent attitude towards his parents' divorce, as well as a desire to help others who have the same problems as himself, namely by giving advice and being a place to tell stories. These two approaches contribute significantly to emotional healing from parental divorce.